2012
DOI: 10.1039/c2an35822k
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescence derivatization method combined with HPLC for determining the activities of endogenous caspase

Abstract: A novel fluorescence derivatization method combined with HPLC was developed to detect the activity of caspase-3 and -8 in two cell lines (Hela cells and A549 cells) which were activated by low temperature-assisted ultraviolet irradiation (LT-UV), mitomycin C (MMC) and camptothecin during the apoptosis, respectively. Two peptide substrates for either caspase-3 or -8 were designed, of which peptide fragments were obtained by enzymatic modification, followed by fluorescence derivatization. A single fluorescent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…With the development of analytical instruments, especially those of hyphenated techniques [e.g., high-performance liquid chromatography with ultraviolet detection (HPLC-UV), high-performance liquid chromatography with mass spectrometry (HPLC-MS) and gas chromatography with mass spectrometry (GC-MS)], the quantitation of compounds and their major metabolites can be produced conveniently. [1][2][3] Enhancing the detection limit, however, is still the key to obtaining information concerning trace components in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of analytical instruments, especially those of hyphenated techniques [e.g., high-performance liquid chromatography with ultraviolet detection (HPLC-UV), high-performance liquid chromatography with mass spectrometry (HPLC-MS) and gas chromatography with mass spectrometry (GC-MS)], the quantitation of compounds and their major metabolites can be produced conveniently. [1][2][3] Enhancing the detection limit, however, is still the key to obtaining information concerning trace components in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance of caspase-3 levels in the apoptotic pathway may promote certain human diseases. Studies of experimental models have suggested that caspase-3 is a reliable indicator of apoptotic rate (1316). However, data concerning the effects of EMF on apoptosis are limited (1).…”
Section: Introductionmentioning
confidence: 99%
“…The active form of caspase-3 can specifically recognize the tetra-peptide motif of Asp-Glu-Val-Asp(DEVD) and hydrolyze the peptide bonds at the C-terminal after the aspartic acid residues. 5 Thereupon, various analytical methods have been developed for the detection and quantification of the caspase-3 activity based on the sequential cleavage activity of the protease employing different techniques, including fluorescence, [6][7][8][9] electrochemistry, 10 chemiluminescence, 11 colorimetry, 12,13 flow cytometry, 14 mass spectroscopy, 15 and surface plasmon resonance. 16 These methods show advantages such as high sensitivity, good biocompatibility for in vivo applications, and good specificity.…”
mentioning
confidence: 99%